Football and dementia: A qualitative investigation of a community based sports group for men with early onset dementia - Carone, Laura; Tischler, Victoria; Dening, Tom (SAGE, 2016)
This study investigates the impact of a weekly group providing sport and physical activities for men with early onset dementia established by Notts County Football in the Community (NCFC). There were three aims: investigate the effect of early onset dementia on individuals with the condition and their carers; examine perceptions of current levels of service provision for people with early onset dementia; and analyse the impact of the group. Men with dementia (n=5) attending the sessions, their carers (n=5), NCFC coaching staff (n=5) and people organising/facilitating the sessions (n=5), were interviewed. Semi-structured interviews explored the participants’ experiences of dementia, their opinions on current service provisions and on the sessions. Data were analysed using thematic analysis. Four main themes were found: loss related to the condition of dementia and its impact on relationships (‘Loss’); lack of age-appropriate services for people with early onset dementia (‘Lack of Resources’); enjoyment and positive anticipation related to the group for all involved (‘Enjoyment and Anticipation’); and ‘the Notts County Effect’ which attributed the success of the sessions to the strong brand of the football club, and to personalised service in a “dementia-free” environment. The NCFC sessions provided a safe low-cost intervention with positive effects upon quality of life for both people with early onset dementia, their carers and the staff involved. This suggests that the service may be valuable to a wider range of people living in different areas